Guanidine N-methylation by BlsL Is Dependent on Acylation of Beta-amine Arginine in the Biosynthesis of Blasticidin S - Wang, Xiankun; Du, Aiqin; Yu, Guiyang; Deng, Zixin; He, Xinyi (Frontiers in Microbiology, 2017)
The peptidyl nucleoside blasticidin S (BS) produced by Streptomyces griseochromogenes was the first non-mercurial fungicide used to prevent rice blast and increasingly used as a selection reagent in transgenic study. Acylation by addition of a leucine residue at the beta amine group of arginine side chain of demethylblasticidin S (DBS) has been proposed as a novel self-resistance to the cytotoxic biosynthetic intermediate. But the resultant product leucyldemethylblasticidin S (LDBS) has not been isolated as a metabolite, and LDBS synthetase activity remained to be demonstrated in S. griseochromogenes. In this study, we isolated LDBS in a BS heterologous producer S. lividans WJ2 upon the deletion of blsL, which encodes a S-Adenosyl methionine-dependent methyltransferase. Purified BlsL efficiently methylated LDBS at the delta N of beta-arginine to generate the ultimate intermediate LBS, but nearly didn’t methylate DBS to final product BS. Above experiments demonstrated that LDBS is indeed an intermediate in BS biosynthetic pathway, and acylation of beta-amino group of arginine side chain is prerequisite for efficient guanidine N-methylation in addition to being a self-resistance mechanism.